Controle genético da taxa de acúmulo de matéria seca em grãos de milhos tropicais - Teixeira, Rita de Kássia Siqueira (2017)
The maize plant yield depends on the number and mass of the grains (MSG) produced. MSG in turn is the product of the number of days from silking to physiological maturation and dry matter accumulation rate in grains per day (TAXA). Although the rate is essencial for the crop success, information about the possibilities of success with selection is scarce. Rare information is restricted to temperate areas. The aims of this study were to verify whether the hybrids in use in Brazil differ in relation to the TAXA; whether this variation is independent of the growing season; whether there is association of TAXA, number of days to silking (NDF), physiological maturity (NDMF) and yield (PROD), and to obtain information on the genetic control of these traits. To achieve this goal, two strategies were used: in the first, a diallel crossing was carried out involving 11 parents, with ten simple hybrids and one population. The 55 hybrid combinations and the parents were evaluated in four experiments conducted in Lavras, MG. In two of them the sowing dates was in November 2014 and October 2015 and the other two in January 2015 and 2016. The following data were collected: the date when the plot had visible silks; dry matter of the grains obtained from ten days after the onset of silking. The samples were taken each seven days until the black layer occurrence. A plant/plot was sampled. In the laboratory, a sample of 100 grains was removed from the central part of the corn cob, obtaining the dry matter. The yield was also obtained at harvest. From these data, the following estimates were obtained: number of days to silking and physiological maturation, daily dry matter accumulation rate. From the averages of these traits and also of the yield the diallel analyzes were realized according to the Gardner and Eberhart (1966) model. It was verified that: there is variability between the parents and hybrids for all traits; no hybrid combination associated early silking with longer grain-filling period and high dry matter accumulation rate in the grains, which is desired. The second strategy evaluated F1 and F2 generations of nine commercial hybrids in contiguous experiments. The data obtained were also NDF, NDMF, TAXA and PROD. The contributions of homozygous (m + a) and heterozygous (d) loci were estimated for each plot. It was verified that most of the variation was explained by the additive effects (m + a) for NDF, NDMF and TAXA traits. The dominance (d) was expressive especially for yield. The hybrids identification with potential for extraction lines is possible if the focus is for any of the traits separately.It is inferred, however, that the use of grain filling rate as auxiliary selective process in order to increase the tropical maize yield should be of low efficiency.